CIVILIZED DEPRAVITY: EVANGELICAL REPRESENTATIONS OF EARLY-NINETEENTH-CENTURY CHINA AND THE REDEFINITION OF "TRUE CIVILIZATION". Issue 2 (25th February 2015) - Fischer, Benjamin; Wagner, Tamara S.
<x content-type="archive" xml:space="preserve">Abstract</x> In the first few decades of the nineteenth century, the experience of missionaries among peoples as diverse as the ancient civilizations of India, the highly organized Zulu kingdoms, and the cannibal tribes of the South Seas had sparked a national debate concerning whether or not the "civilization of the heathen" was necessary before they could be converted, or whether Christianity would be the best means of civilizing them. Unresolved as far as public policy was concerned, this question entered discussions of the 1835 Select Committee on Aboriginal Tribes (British Settlements), a committee convened to address problems arising between British settlers and indigenous communities, including important trade sites in Australia, New Zealand, and the islands of the Pacific. As with several other areas where significant British imperial pressure never took the form of direct colonial rule, the trade ports in China fell outside the committee's explicit considerations. Along with forbidding foreign settlements, Chinese culture did not fit the terms or assumptions of the committee's conversation. Since the first Jesuit mission to China in the late sixteenth century, there had been little doubt in Europe that Chinese civilization was far advanced. As a tightly controlled bureaucratic state confident of its own position as the Middle Kingdom of the world, China simply did not work within the discourse of civilization. This essay explores one attempt to adjust the terms of that British discourse in order to accommodate a civilized China.